Ciclo de vida del barrenador del ápice (díptera: anthomyiidae) como plaga del chocho, en la provincia de Cotopaxi, periodo 2017 - Corrales Sánchez, Juan José (2017)
This research deals with the description of the Life Cycle of the Chop Apex Borer (Lupinus mutabilis Sweet) in Laboratory of Entomology of the Technical University of Cotopaxi. (Latitude: 00 ° 59 "47.68" S, Longitude: 78 ° 37 "19.16" E). The study begins with the collection of the species to be identified and described. For this reason, plants with the typical symptoms of the attack of the apex borer were identified. These are the perforations of the stems, dwarfism and yellowing, brown and violet colorations with greater intensity throughout plant. It is therefore interesting that the Life Cycle of the Apex Borer is 50 days, housed in chambers in wood boxes covered with cloth tool, in them plants of puff in mastets and honey with water for food. Results related to the stages that cause more damage to the plant were larvae and adults, the larva feeds inside the stalk thus forming galleries "mines" and weakening the structure of the plant, the adult is the cause of the perforation of leaves for and also to increase the population by ovipositing eggs. For the study we considered all possible stages of visualization per plant that is the unit of study since the species developed all its processes in a living plant. Identified its stages was made to the description of its morphological characteristics, in egg in its oval form of white color, in larva body elongated its head of black color and its buccal parts have forms of hooks, in pupa in the form of barrel of whitish color And the adult his description were divided into three head, thorax and abdomen each of those were described.